SMART FARMING IN BRAZIL: AN OVERVIEW OF TECHNOLOGY, ADOPTION AND FARMER PERCEPTION - Pivoto, Dieisson; Laimer, Claudionor Guedes; Mores, Giana De Vargas; Waquil, Paulo Dabdab; Talamini, Edson; Dalla Corte, Vitor; De Matos, Everton (Revista Brasileira de Gestão e Desenvolvimento Regional, 2023)
At the second decade of the 21st century, the use of a new set of agricultural technologies, such as smart farming (SF), emerge among agribusiness organizations and agents. This study aims to identify the smart farming technologies used in grain production systems in Brazil and to verify the perception of the farmers regarding technical assistance for SF. A survey was conducted with farmers and 119 valid observations were collected. The study used non-probabilistic sampling, since it considered grain farmers whose farms produced more than 50% of their gross revenue in grains. Descriptive and content analysis were used to analyze the data. The results indicate that soil sampling is the main precision agriculture technology adopted by the production systems assessed, while smartphone applications to assist in agricultural management are the most used information technology. The machines used in grain production systems are undergoing a digitization process, especially due to the increase in availability of equipment with sensors and automated processes. However, the question remains about the capacity of farmers and assistance agents to monitor and take advantage of the potential of SF technologies in farms.